Predicting the functional and structural consequences of nsSNPs in human methionine synthase gene using computational tools. (4th July 2019) - Desai, Mansi; Chauhan, Jenabhai B.
ABSTRACT: Methionine synthase encoded by the MTR gene is one of the key enzymes involved in the SAM (S- Adenosyl Methionine) cycle catalyzing the conversion of homocysteine to methionine. Methionine plays an important role in the DNA, RNA, protein, phospholipids, and neurotransmitters methylation. It also maintains serum homocysteine level and indirectly regulates de novo nucleotide synthesis and repair. The current study predicted the functional consequences of nsSNPs in human MTR gene using SIFT, PolyPhen2, PROVEAN, SNAP2, PMut, nsSNPAnalyzer, PhD-SNP, SNPs&GO, I-Mutant, MuPro, and iPTREE-STAB. The PTM sites within the protein were predicted using ModPred and the phylogenetic conservations of amino acids & conserved domains of protein were predicted using ConSurf and NCBI conserved domain search tool respectively. The protein 3D structure was generated using SPARKS-X and analyzed using RAMPAGE. Structural deviation was analyzed using TM-Score. STRING analysis was preformed to predict protein-protein interactions. D621G, G682D, V744L, V766E, and R1027W were predicted to be the most deleterious nsSNPs in MTR . R1027 was predicted to having the three PTM sites and G682 & V744 were predicted as highly conserved residues. D621G, G682D, V744L, V776E, and R1027W were predicted to be within conserved domains of methionine synthase. The G682D, V744L, V776E,   and R1027W were predicted to alter protein 3D structure. STRING predicted that methionine synthase interacting with 10 different proteins. The present study predicted D621G, G682D, V744L, V766E, and R1027W as functionally and structurally significant nsSNPs in human MTR gene. The present study can provide the significant information for further experimental analysis. Abbreviations: cblG: methylcobalamin deficiency G; MTR: 5-methyl tetrahydrofolate-homocysteine methyl transferase; MS: methionine synthase; SAM: S-adenosyl methionine; nsSNPs: non-synonymous single nucleotide polymorphisms; OMIM: online mendelian inheritance in man; NCBI: national center for biological information; SIFT: sorting intolerant from tolerant; PolyPhen2: polymorphism phenotyping 2; PROVEAN: protein variation effect analyzer; SNPs&GO: single nucleotide polymorphisms and gene ontology; PhD-SNP: predictor of human deleterious single nucleotide polymorphisms; RI: reliability index; PTM: post translational modification; SPDBV: Swiss PDB viewer; PDB: protein data bank; RMSD: root mean square deviation; STRING: search tool for the retrieval of interacting proteins